Pregnancy Prevalence and Outcomes in U.S. Jails - Sufrin, Carolyn (Obstet Gynecol, 2020)
OBJECTIVE: To describe the number of admissions of pregnant people to U.S. jails and the outcomes of pregnancies that end in custody. METHODS: We prospectively collected pregnancy data from 6 U.S. jails, including the 5 largest jails, on a monthly basis for 12 months. Jails reported de-identified, aggregate numbers of pregnant people admitted, births, preterm births, cesarean deliveries, miscarriages, induced abortions, ectopics, and maternal and newborn deaths. RESULTS: There were 1622 admissions of pregnant people in 12 months in the selected jails. The highest one-day count of pregnant people at a single jail was 65. The majority of these admissions involved the release of a pregnant person. Of the 224 pregnancies that ended in jail, 144 (64%) were live births, 41 (18%) were miscarriages, 33 (15%) were induced abortions, and 4 were ectopics (1.8%). One third of the births were cesarean deliveries and 8% were preterm. There were 2 stillbirths, 1 newborn death, and no maternal deaths. CONCLUSIONS: About 3% of admissions of females to U.S. jails are of pregnant people; extrapolating study results to national female jail admission rates suggests nearly 55,000 pregnancy admissions in 1 year. It is feasible to track pregnancy statistics about this overlooked group..